EXPERIMENTAL INVESTIGATION INTO SURGE BEHAVIOR OF TURBOCHARGER CENTRIFUGAL COMPRESSORS WITH LOCAL GEOMETRY VARIATIONS - Stuart, Charles (My University, 2026)
Surge is a flow instability phenomenon that limits the stable operating range of centrifugal compressors at low flow rates, posing a significant threat to compressor aerodynamic performance and safe operation. This paper presents an experimental study of surge behavior in three ported shroud equipped turbocharger centrifugal compressors with local geometry variations in ported shroud strut length and diffuser recess size. The experiments include the measurement of the stage performance map, interstage static pressure validation, and dynamic pressure characteristics during the throttling process towards surge boundaries. The results showed that even minor geometry variations in non-core components can significantly affect the compressor performance map width. Two distinct surge behaviors were identified: (i) TYPE A: the compressor experienced a surge island, characterized by mild surge, stability recovery, and deep surge eventually; (ii) TYPE B: the compressor directly evolved from mild surge into deep surge. The stability parameter (SP) of compressor sub-components was evaluated using a previously developed numerical model, revealing a strong correlation between impeller stability variation and the onset of mild surge. The underlying mechanism is that, as the flow rate reduces, a recirculating bubble is formed at the shroud side within the impeller exducer, which deteriorates impeller stability and triggers the onset of mild surge. The formation of the surge island is attributed to the partial removal of this recirculating bubble as it extends upstream to the ported shroud bleed slot with further flow rate reduction, which temporarily restores impeller stability and enables the compressor to recover from mild surge. To the best of the authors’ knowledge, this study is the first to present the interaction between the recirculating bubble at impeller exducer shroud endwall and the ported shroud bleed slot, and to interpret the mechanisms of surge behaviors in ported shroud equipped centrifugal compressors. The research provides new insights for improving centrifugal compressor stability.
ASME Turbo Expo 2026 Turbomachinery Technical Conference and Exposition
PUBLISHED
Milan, Italy
Keywords: Turbocharger Compressor; Ported Shroud; Surge Behavior; Experiment; Aerodynamics; Mechanical Engineering